2017
DOI: 10.24200/sci.2017.20022
|View full text |Cite
|
Sign up to set email alerts
|

An Optimization Model for Emergency Vehicle Location and Relocation with Consideration of Unavailability Time

Abstract: The main purpose of emergency medical services is providing fast medical care, as well as transporting patients to the hospital, in the shortest possible time. Healthcare managers try to improve healthcare systems through reducing the response to demand time. In this paper, we seek to propose an optimization model in order to cover as much demand as possible in the shortest possible time using the available ambulance fleet. To do so, considering the response and service time, amount of demand during the time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Enayati et al [110] proposed a real-time optimization to tackle managerial decisions related to ambulance fleets. In their model, the authors implement two linear programming models in series.…”
Section: Modeling Issuesmentioning
confidence: 99%
See 3 more Smart Citations
“…Enayati et al [110] proposed a real-time optimization to tackle managerial decisions related to ambulance fleets. In their model, the authors implement two linear programming models in series.…”
Section: Modeling Issuesmentioning
confidence: 99%
“…For example, Tsai et al [89] use time series smoothing to tackle stochasticity to make better relocation decisions. Other researchers deal with demand stochasticity with hypercube models like in [100,110,114,115,126,128]. Other studies deal with stochasticity in travel times using machine learning [130], as Olave-Rojas and Nickel [131] have previously done.…”
Section: Modeling Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they used a discrete-event simulation approach, and concluded that their innovative strategy would reduce the probability of tardiness. Firooze et al 10 presented a multi-period dynamic model, in which the dispatch strategies for idle ambulances and the redeployment strategies for ambulances having completed their missions are defined. The proposed model minimizes response time by considering the proper redeployment of the ambulances.…”
Section: Introductionmentioning
confidence: 99%